Rancangan Perbaikan Penataan Gudang di PT. Bondi Syad Mulia - Ardenus Milton Setiadi; Jani Rahardjo (Jurnal Titra, 2015)
PT. Bondi Syad Mulia is a company which provides galvanized for iron. Based on the observation, there is an issue on placing and storing the goods in the warehouse. This research is to solve the problem by re-organizing the layout and placing the label in warehouse division in PT. Bondi Syad Mulia. The proposed layout covers the arrangement of goods in the warehouse of materials and tools by considering the FMS classification. The improvement on labeling system was done by labeling of goods and a place for storing goods. The momen result of the proposed layout was reduced by 34,25%. After labelling was placed, the result showed that there was 10 second reduction on taking the files and 30 second reduction on taking the goods from the rack.